Electricity, hot water and cold water production from biomass. Energetic and economical analysis of the compact system of cogeneration run with woodgas from a small downdraft gasifier - Coronado, Christian Rodriguez [UNESP]; Yoshioka, Juliana Tiyoko [UNESP]; Silveira, Jose Luz [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Wood gasification technologies to convert the biomass into fuel gas stand out. on the other hand, producing electrical energy from stationary engine is widely spread, and its application in rural communities where the electrical network doesn't exist is very required. The recovery of exhaust gases (engine) is a possibility that makes the system attractive when compared with the same components used to obtain individual heat such as electric power. This paper presents an energetic alternative to adapt a fixed bed gasifier with a compact cogeneration system in order to cover electrical and thermal demands in a rural area and showing an energy solution for small social communities using renewable fuels. Therefore, an energetic and economical analysis from a cogeneration system producing electric energy, hot and cold water, using wooden gas as fuel from a small-sized gasifier was calculated. The energy balance that includes the energy efficiency (electric generation as well as hot and cold water system; performance coefficient and the heat exchanger, among other items), was calculated. Considering the annual interest rates and the amortization periods, the costs of production of electrical energy, hot and cold water were calculated, taking into account the investment, the operation and the maintenance cost of the equipments. Crown Copyright (C) 2010 Published by Elsevier Ltd. All rights reserved.
Keywords: Biomass gasification; Internal combustion engine; Cogeneration; Energy efficiencies; Costs